MARTX Toxin in the Zoonotic Serovar of Vibrio vulnificus Triggers an Early Cytokine Storm in Mice - Murciano, Celia; Lee, Chung-Te; Fernández-Bravo, Ana; Hsieh, Tsung-Han; Fouz, Belén; Hor, Lien-I; Amaro, Carmen (Frontiers in Cellular and Infection Microbiology, 2017)
Vibrio vulnificus biotype 2-serovar E is a zoonotic clonal complex that can cause death by sepsis in humans and fish. Unlike other biotypes, Bt2 produces a unique type of MARTXVv (Multifunctional-Autoprocessive-Repeats-in-Toxin; RtxA13), which is encoded by a gene duplicated in the pVvBt2 plasmid and chromosome II. In this work, we analyzed the activity of this toxin and its role in human sepsis by performing in vitro, ex vivo, and in vivo assays. First, we demonstrated that the ACD domain, present exclusively in this toxin variant, effectively has an actin-cross-linking activity. Second, we determined that the whole toxin caused death of human endotheliocytes and monocytes by lysis and apoptosis, respectively. Finally, we tested the hypothesis that RtxA13 contributes to human death caused by this zoonotic serovar by triggering an early cytokine storm in blood. To this end, we used a Bt2-SerE strain (R99) together with its rtxA13 deficient mutant, and a Bt1 strain (YJ016) producing RtxA11 (the most studied MARTXVv) together with its rtxA11 deficient mutant, as controls. Our results showed that RtxA13 was essential for virulence, as R99ΔΔrtxA13 was completely avirulent in our murine model of infection, and that R99, but not strain YJ016, induced an early, strong and dysregulated immune response involving the up-regulation of a high number of genes. This dysregulated immune response was directly linked to RtxA13. Based on these results and those obtained ex vivo (human blood), we propose a model of infection for the zoonotic serovar of V. vulnificus, in which RtxA13 would act as a sepsis-inducing toxin.